The effect of ethanol on pre-zygotic barriers between Drosophila melanogaster and D. simulans - Persson,Linus (2025)
Sexually reproducing species tend to have reproductive barriers between them that prevent hybrid offspring from being formed. Drosophila melanogaster and D. simulans are two closely related species that can form sterile hybrids. In addition to their post-zygotic barriers, which cause the hybrid sterility, some behavioral pre-zygotic barriers also exist. These include different preferences for courtship songs and pheromone profiles. These species are cosmopolitan and come into close contact with each other and to ethanol, both through their mating locations on (over)ripe fruits and their proximity to breweries in cities. Ethanol is known to generally affect sexual behavior and at lower doses it tends to cause sexual disinhibition. Previous studies have indicated that both these species become sexually disinhibited toward conspecific potential mates when exposed to significant levels of ethanol. Here, I investigate whether this phenomenon extends interspecifically and whether their behavioral reproductive barriers are affected. I paired simulans males with both simulans and melanogaster females, separately. For both the conspecific and heterospecific pairings, I created four different treatment combinations where either sex was sober or intoxicated. In the conspecific pairing, I find that female ethanol treatment significantly increased the number of courtships but decreased offspring. In the heterospecific pairing, female ethanol treatment did seem to increase courtship, while male intoxication caused a near cessation of courtship and a reduction in offspring counts . The most surprising result was that ethanol affected male sexual behavior very differently depending on female species. I provide a mechanistic hypothesis for this finding and speculate on the evolutionary and ecological implications of my results.